2010
DOI: 10.1248/bpb.33.1494
|View full text |Cite
|
Sign up to set email alerts
|

7-O-Methylaromadendrin Stimulates Glucose Uptake and Improves Insulin Resistance in Vitro

Abstract: The much more common condition of diabetes mellitus (DM) is type 2 DM, which represents 90 to 95% of all diagnosed cases of diabetes.1) Insulin resistance, a specific feature of type 2 DM, is the condition whereby major organs such as muscle and liver become resistant to the action of the hormone, leading to increased glucose output from the liver and reduced uptake and metabolism of glucose by other organs. 2)Studies on the molecular basis of insulin resistance have focused on the peroxisome proliferator-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…Kinetic studies demonstrated that the inhibition produced by the flavonoid mixture and pheophytin A as well as the TFMS inhibitor of PTP1B enzyme indicates they were competitive inhibitors. Such compounds from plants including phenols, flavonoids and other compounds have been reported as PTP1B inhibitors (Zhang et al, 2010;Na et al, 2006a, b). These reports show that PTP1B enzyme inhibiting compounds from plants belong to diverse chemical classes.…”
Section: Discussion and Conclusionconclusionmentioning
confidence: 99%
“…Kinetic studies demonstrated that the inhibition produced by the flavonoid mixture and pheophytin A as well as the TFMS inhibitor of PTP1B enzyme indicates they were competitive inhibitors. Such compounds from plants including phenols, flavonoids and other compounds have been reported as PTP1B inhibitors (Zhang et al, 2010;Na et al, 2006a, b). These reports show that PTP1B enzyme inhibiting compounds from plants belong to diverse chemical classes.…”
Section: Discussion and Conclusionconclusionmentioning
confidence: 99%
“…The glucose uptake assay using the 2-NBDG screening system was performed as described previously (Zhang et al 2010). Briefly, IEC-6 cells were seeded at 1 × 10 4 cells/well into 96-well plates for 24 h and then treated with or without a given concentration of dexamethasone and 50 µM of the SGK1 inhibitor EMD638683 in the absence or presence of 100 µM 2-NBDG for 1 h. The fluorescence intensity of 2-NBDG was recorded in the FL1 channel using a FACScaanto TM flow cytometer (Becton Dickinson, Franklin Lakes, NJ, USA).…”
Section: Glucose Uptake Measurement Using Flow Cytometrymentioning
confidence: 99%
“…Insulin-resistant HepG2 cells were induced with high glucose as described previously [12,13,24,25] with minor modifications. Briefly, 3 !…”
Section: Induction Of Insulin-resistant Hepg2 Cells and Immunoblottingmentioning
confidence: 99%